2011
DOI: 10.1186/1471-2474-12-268
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of deep tissue hypersensitivity to pressure pain in professional pianists with insidious mechanical neck pain

Abstract: BackgroundThe aim of this study was to investigate whether pressure pain hyperalgesia is a feature of professional pianists suffering from neck pain as their main playing-related musculoskeletal disorder.MethodsTwenty-three active expert pianists, 6 males and 17 females (age: 36 ± 12 years) with insidious neck pain and 23 pianists, 9 males and 14 females (age: 38 ± 10 years) without neck pain the previous year were recruited. A numerical pain rate scale, Neck Disability Index, hand size and pressure pain thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…injuries and illnesses during a band camp [174]. There were also 12 case-control studies [96,97,110,111,115,140,141,[162][163][164][165]178]. Of these case-control studies, 3 included a playing-task [111,115,178], 1 resisted finger extension/flexion [165], and another emotionally and physically stressful tasks [110].…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…injuries and illnesses during a band camp [174]. There were also 12 case-control studies [96,97,110,111,115,140,141,[162][163][164][165]178]. Of these case-control studies, 3 included a playing-task [111,115,178], 1 resisted finger extension/flexion [165], and another emotionally and physically stressful tasks [110].…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%
“…playing-related pain. [17][18][19][20][21][22] However, 2 systematic reviews among musicians 12,23 found no consistent results regarding these features, which might be due to the diversity of anthropometric aspects they included.…”
Section: Relationships Have Been Reported Between Anthropometric Featmentioning
confidence: 99%
“…About 0.6% of the general population is exposed to disability caused by IOMNP and females are more prone to recurrent and / or chronic pain than males [3]. The IOMNP can be considered a work-related disorder in some professions, including pilots [4][5][6][7], musicians [8][9], and workers using personal computer for prolonged times [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…About 0.6% of the general population is exposed to disability caused by IOMNP and females are more prone to recurrent and / or chronic pain than males [3]. The IOMNP can be considered a work-related disorder in some professions, including pilots [4][5][6][7], musicians [8][9], and workers using personal computer for prolonged times [10][11][12][13][14].Cervical spine supports the head and orients it in space, transmits forces on the upper limb and has close relations with the visual and vestibular function [15][16][17][18]. Given the complexity of this region and the close link between central nervous system (CNS) and muscles, several abnormalities in structure and function of the neuromuscular system may develop when pain occurs [2,15].…”
mentioning
confidence: 99%